1997
DOI: 10.1152/ajpheart.1997.272.1.h176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitric oxide synthase inhibitors on endothelial [Ca2+]i and microvessel permeability

Abstract: To investigate the mechanism whereby nitric oxide (NO) signaling pathways regulate microvessel permeability in vivo, we measured changes in microvessel hydraulic conductivity (Lp) and endothelial cytoplasmic calcium concentration ([Ca2+]i) in response to calcium ionophore, ionomycin (5 microM), and ATP (10 microM) before and after the use of NO synthase (NOS) inhibitors in single perfused frog mesenteric venular microvessels. Ionomycin induced a transient increase in endothelial [Ca2+]i and an associated incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
50
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 0 publications
7
50
0
Order By: Relevance
“…It even inhibits agonist-induced permeability increases without altering an agonist-induced increase in endothelial [Ca 2ϩ ] i . While agents like cAMP, cGMP agonist, and eNOS inhibitor regulate permeability downstream from the initial Ca 2ϩ signals (10,11), these modulators do not affect the agonist-induced increases in endothelial [Ca 2ϩ ] i , similar to S1P. However, unlike S1P, these agents alone have no effect on endothelial [Ca 2ϩ ] i .…”
Section: Discussionmentioning
confidence: 96%
“…It even inhibits agonist-induced permeability increases without altering an agonist-induced increase in endothelial [Ca 2ϩ ] i . While agents like cAMP, cGMP agonist, and eNOS inhibitor regulate permeability downstream from the initial Ca 2ϩ signals (10,11), these modulators do not affect the agonist-induced increases in endothelial [Ca 2ϩ ] i , similar to S1P. However, unlike S1P, these agents alone have no effect on endothelial [Ca 2ϩ ] i .…”
Section: Discussionmentioning
confidence: 96%
“…Regarding the role of shear stress in microvascular permeability, NO release by endothelial cells has been suggested to be an important mechanism (3). Investigations performed on individually perfused microvessels indicated that L p is decreased by NOS inhibition (12,35,36). However, it also should be noted that the application of NOS inhibitors can induce an increase in leukocyte adhesion to venular endothelium and a subsequent increase in L p in autoperfused capillaries when L-NAME (at a concentration of 100 M) is treated for longer periods of time (20 min) (10).…”
Section: Vascular Proteinmentioning
confidence: 99%
“…In the small intestine, NADPH-diaphorase histochemical staining and nNOS immunoreactivity (nNOS-IR) have been demonstrated in perivascular nerves (34,35,41,49), but isoform-specific localization of NOS within the amphibian mesenteric vasculature has not been performed. There is evidence in amphibians that NO is involved in capillary fluid regulation, inasmuch as inhibition of NOS has been reported to decrease hydraulic conductivity (55) and capillary permeability (23,24,54) in the mesenteric circulation of the leopard frog Rana pipiens. Furthermore, substance P (SP) increased microvascular permeability in R. pipiens by increasing NO production (44).…”
mentioning
confidence: 99%